Early findings on home delivery of buprenorphine and retention in treatment for opioid use disorder - Marlene C. Lira; Lauren E. Hendy; Alisha Liakas; Laura Turanchik; Clare Pritchard; Cynthia Jimes; M. Justin Coffey (Addiction Science & Clinical Practice)
Abstract Individuals with opioid use disorder face barriers accessing first-line pharmacotherapy. Home delivery interventions have been shown to improve medication adherence for other chronic diseases, but the relationship between buprenorphine home delivery and opioid use disorder treatment outcomes has not been assessed. We evaluated the association between medication home delivery and retention in treatment in a feasibility study of adults who initiated telemedicine treatment for opioid use disorder and received one or more prescriptions. We described the characteristics of patients and estimated the odds of attending a telemedicine visit three and six months after enrollment as a function of home delivery use using logistic regression. The sample consisted of 337 adults with the following characteristics: mean age 40.8 years (SD 10.1), 51.0% male, and 70.9% commercially insured. In the first 30 days of treatment 6.8% (n = 23) of patients used home delivery. At three months, the percentages of individuals retained among those with and without home delivery were 82.6% and 58.9%, respectively (odds ratio [OR]: 3.31, 95% confidence interval [CI]: 1.10–9.96). At six months, the percentages of individuals retained among those with and without home delivery were 78.6% and 45.5%, respectively (OR: 4.39, 95% CI: 1.19–16.25, n = 203). Although uptake of medication delivery through the pharmacy partner was low within this sample of patients receiving treatment for opioid use disorder, its use was associated with increased retention in care at three and six months. Given the small sample size, low uptake, and limited statistical power, additional research is warranted.